Epidemiological profile of human visceral leishmaniasis in the state of Mato Grosso, Brazil - 2010 to 2020 (Research, Society and Development, 2022)
Objective: to describe the epidemiological profile of cases of Visceral Leishmaniasis (VL) reported in the state of Mato Grosso, Brazil, from 2010 to 2020. Methods: quantitative-descriptive study of data obtained from the Notifiable Diseases Information System (SINAN). Results: From 2010 to 2020, 318 cases of VL were reported; 66.35% of individuals were male; 56.29% declared themselves brown color; 37.74% were children aged ≤10 years; 43.82% completed elementary school and 85.54% lived in urban areas. The LV/HIV coinfection rate was 10.06%; 91.82% presented fever; 11.32% of cases evolved to death, 26.67% of individuals over 60 years of age and 65.09% occurred in the region of Rondonópolis. Conclusion: The study aims to the need to improve heath surveillance and control actions for the disease and its vectors, in addition to health education actions, especially among the most affected population.